Observation Study of Stratiform Precipitation and Cloud Microphysical Structures During a Flight Detection Over Liupan Mountain Areas - Tian, Lei; Chang, Zhuolin; Zhu, Haoran; lin, Tong; Cao, Ning; Sun, Yanqiao (Journal of Progress in Civil Engineering, 2025)
A flight detection with stratiform precipitation on September 19th, 2018 is chosen for analysis. Through the level flight, circling and repeated detection after seeding, the cloud structures of Liupan mountain is profiled. The microphysical structures of stratiform clouds, the precipitation enhancement conditions as well as physical responses after cloud seeding are studied. The results show that the thickness of mixed clouds are larger than 5km, interlayer is found in mixed clouds, the 0℃ temperature layer is at a height range of 4800-5000 m. There are significant differences between the macro and micro physical structures at East and West side of Liupan mountains and surface precipitation can be seen in both sides. At West side of Liupan Mountain, the clouds which contain three layers are thicker, the upper two layers are mainly formed by ice particles, the spectrum of particle size is wide, the number concentration is comparatively small, precipitation is mainly from bottom layer of mixed clouds, the supercooled water lead to enhanced condensation growth. At East side of Liupan Mountain, there is no interlayer, the increase of cloud particles is milder than West side. Supercooled water exist in the top and middle part of stratiform cloud, which is suitable for cold cloud seeding operations.